Identification of groundwater potential zones using AHP in district Kuala Krai, Kelantan, Malaysia. Issue 1 (August 2021) - Jamil, R M; Hisham, S S; Leong, M C; Nawawi, S A; Nor, A N M; Ibrahim, N
Abstract: Groundwater is one of the main sources of water in Kelantan which consumes 70% of the water supply. The rapid development in population, urbanization, agriculture, and industry has led to an increased water supply and demand. Hence, it is necessary to identify new groundwater potential sources to enhance groundwater supply in the study area. This study was carried out at Kuala Krai, Kelantan within latitude 5"36'30° to 5"33'50° N and longitude 102"8'25° to 102"11'10° E. The Analytical Hierarchy Process (AHP) method were used in this study and this method eventually come out with groundwater potential zones. The parameters such as lithology, geomorphology, land use, slope, drainage density, rainfall density, and soil type were chosen and spatially generated using GIS platform. Those parameters were subjected to weighted overlay analysis to obtain the potential zones of groundwater. The weights for the various layers were generated and assigned using the AHP technique which allows the comparison of criteria influencing the potential zone. The results of the study revealed that the good potential zone comprises 36.1%, moderate 32.4%, and poor 31.5% areas respectively. In conclusion, factors such as low elevation, gentle slope, alluvial plains, and vegetation area have given a high potential of groundwater in this study area.